The status of transsexual people in Iceland : sociodemographic and clinical characteristics, psychological well-being, self-esteem and quality of life - Katrín Ella Jónsdóttir 1987- (2016)
Gender dysphoria and transsexualism is a growing research field but so far there is no published data available on this minority group in Iceland. The aim of this study was to examine and provide data on the characteristics of transsexual people in Iceland. The participants in this descriptive study included 22 individuals, 13 trans women and 9 trans men, ranging from 18 to 63 years of age, who were at different points in the sex reassignment process. They were interviewed and answered psychological scales about their sociodemographic and clinical characteristics. Half of the participants were married or in a relationship, but this applied only to the trans women as well as having biological children. The trans men were more often sexually attracted to the same biological sex. There was a high rate of unemployment among the participants, but a low rate of depression and anxiety symptoms. Participants who were further along in the sex reassignment process reported better self-esteem and quality of life. Despite limitations of small sample size this study provides important knowledge about transsexual people in Iceland and can constitute a ground for further research in this field in Iceland.